The Impact of Long Drought on the Increase in Fertilizer Prices and Rice Prices in Nganjuk Regency: Dry Season, Fertilizer Prices, Price of Rice - Siska Marlina; Kasimun (EkoPreneur, 2024)
Agriculture is the second largest economic support sector in Indonesia as it serves as a food provider, employment and source of income. The long dry season significantly affects rice prices and rice production compared to the rainy season. This study aims to determine the effect of the long dry season and the increase in fertilizer prices that greatly influenced the increase in rice prices in Nganjuk Regency. The research method used was a descriptive qualitative method. The technique of collecting data through observation, questionnaires and interviews, namely data regarding information and explanations from farmers. The causes of rice price increases are reduced agricultural production, reduced agricultural labor, the influence of the season, increased fertilizer prices, increased agricultural needs, the emergence of rice pests and increased fuel oil (BBM) and reduced agricultural land area. Policies made by the government aim to protect farmers from falling grain prices during the harvest season. The outcome of the research is the existence of a policy from the government for farmers in the event of a long drought on the increase in rice prices in Nganjuk Regency so that grain prices can be resolved during the main harvest.